Perlindungan Hukum Pemegang Hak Atas Tanah terhadap Pendirian Lembaga Rechtsverwerking - Marina Satya (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2021)
The purpose of this research is to investigate the implementation of rechtsverwerking (waiver of right) institution and to investigate the legal protection for land rights holders because of the implementation of the rechtsverwerking institution. The current research approach is a normative-empirical juridical approach. This type of research is live case study research (especially the implementation of rechtsverwerking legal institutions in Biak Numfor District), implementing normative legal provisions that refers to certain legal events occurring in a society. The data collection technique carried out by studying literatures with respect to various regulations and other related documents for this current research. Qualitative analysis is employed in analyzing the existing data. The research findings demonstrated that Biak’s Regional Land Agency has not fully implemented Law No 5/1960 concerning Basic Agrarian Regulations and Government Regulation No. 24/1997 concerning Land Registration. In addition, some land disputes (customary land) are resolved through traditional law (adat law), holding traditional rituals to honor the ancestors. Traditional dispute resolution is represented to Rechtsverwerking institution.